Reversibly Alterable Hot-Electron Photodetection Without Altering Working Wavelengths Through Phase-Change Material Sb2S3 - Yaoyao Li; Xiaoyan Yang; Jia Hao; Junhui Hu; Qingjia Zhou; Weijia Shao (Micromachines)
Generally, the responsivities of hot-electron photodetectors (HE PDs) are mainly dependent on the device working wavelengths. Therefore, a common approach to altering device responsivities is to change the working wavelengths. Another strategy for manipulating electrical performances of HE PDs is to harness electric bias that can be used to regulate hot-electron harvesting at specified working wavelengths. However, the reliance on bias hampers the flexibility in device operations. In this study, we propose a purely planar design of HE PDs that contains the phase-change material Sb2S3, realizing reversibly alterable hot-electron photodetection without altering the working wavelengths. Optical simulations show that the designed device exhibits strong absorptance (>0.95) at the identical resonance wavelengths due to the excitations of Tamm plasmons (TPs), regardless of Sb2S3 phases. Detailed electrical calculations demonstrate that, by inducing Sb2S3 transitions between crystalline and amorphous phases back and forth, the device responsivities at TP wavelengths can be reversibly altered between 59.9 nA/mW to 128.7 nA/mW. Moreover, when device structural parameters are variable and biases are involved, the reversibly alterable hot-electron photodetection at specified TP wavelengths is maintained.